Changes in nutritional status of patients with jaw deformities due to orthognathic surgery - Inaba, Yoshinori; Hasebe, Daichi; Hashizume, Kosuke; Suda, Daisuke; Saito, Naoaki; Saito, Daisuke; Sakuma, Hidenobu; Funayama, Akinori; Kobayashi, Tadaharu (Oral surgery, oral medicine, oral pathology and oral radiology, 2023)
In orthognathic surgery, it is important to carefully manage peri-operative nutrition because maxillomandibular fixation and problems such as swelling and pain after surgery may make it difficult to eat normally and may prevent adequate nutrition. This study investigated the changes in nutritional status of patients with jaw deformities due to orthognathic surgery. The subjects were 155 jaw deformity patients, who underwent orthognathic surgery. The nutritional status was evaluated using anthropometry immediately before and 10 days after surgery and clinical laboratory results and the controlling nutritional status (CONUT) score before surgery and immediately, 1 week and >6 months after surgery. We investigated the relationship among the nutritional status, surgical procedures, and dietary intake in patients who underwent orthognathic surgery. The surgical procedure time and amount of bleeding were significantly greater as the surgical procedure became more complex. All of the laboratory values and CONUT scores were significantly decreased immediately after surgery and then increased over time, recovering to the same level as before surgery except for serum albumin at >6 months after surgery. Nutritional management is considered as one of the key factors for the better and faster recovery after the orthognathic surgery.